Managing reverse logistics to enhance sustainability of industrial marketing - Lam, Jasmine Siu Lee (2013)
In this paper, a sustainable industrial marketing framework of latest requirement of green and sustainable operation is proposed. When literatures in strategy, marketing and operation have provided insight about the efficiency of reverse logistics and business value for the customer, the interrelationship is still under explored. This raises the question whether manufacturers could determine ecological friendly strategies to address their customer's environmental conscious needs and design the suitable solution to strike the balance between ecology and economics. Based on the case study of a medical product manufacturer, this study addresses this question by investigating how manufacturers identify the problem of reverse logistics; design and develop of sustainable product and service by enhancing the efficiency of operations, and market competencies that add value to their customers' business processes. Within the strategy for designing for effective reverse logistics, these findings contribute to understand the use of information system and technology for reverse logistics to enhance the customer's business process and provide value-added process for customer retention.